Chemical profile and nutraceutical features of Salsola soda (agretti): Anti-inflammatory and antidiabetic potential of its flavonoids. (October 2020) - Iannuzzi, Anna Maria; Moschini, Roberta; De Leo, Marinella; Pineschi, Carlotta; Balestri, Francesco; Cappiello, Mario; Braca, Alessandra; Del-Corso, Antonella
Abstract: The chemical profile and the nutraceutical features of cultivated Salsola soda buds, in comparison with the wild plant, were investigated. Four flavonoids, rutin (1 ), quercetin 3- O -glucuronopyranoside (2 ), isorhamnetin 3- O -rutinoside (3 ), and isorhamnetin 3- O -glucuronopyranoside (4 ), were isolated from the wild S. soda and tested to target three human recombinant enzymes, i.e., aldose reductase ( h AKR1B1), aldose-reductase-like protein ( h AKR1B10), and carbonyl reductase 1 ( h CBR1). Furthermore, three saponins, namely momordin IId (5 ), momordin IIc (6 ), and dihexosyl-pentosyl-glucuronosyl oleanolic acid (7 ) were identified in the plant and tested together for inhibitory activity of h AKR1B1. While no inhibitory activity was measured for the saponin mixture, flavonoids were shown to be able to inhibit the three target enzymes. Compound 2, the only flavonoid significantly represented in the cultivated edible S. soda, was shown to be the most effective inhibitor of the target enzymes. Indeed, it resulted in an appreciable inhibition of both h AKR1B1 and h CBR1, acting as an uncompetitive ( K i ', 0.97 ± 0.24 μ M ) and as a mixed noncompetitive inhibitor ( Ki, 0.84 ± 0.04; Ki', 0.51 ± 0.05 μM), respectively. These results suggested the potential of S. soda components to favorably intervene in pathological conditions linked to diabetic complications, inflammatory processes, and in cancer therapy. Highlights: Four flavonoids and three saponins are identified in Salsola soda aerial parts. Aldose reductase, aldose reductase-like and carbonyl reductase1 are targeted. Quercetin 3- O -glucuronopyranoside is active on the three target enzymes. Quercetin-3- O -glucuronopyranoside confers nutraceutical features to Salsola .